Crucial Importance of Work Productivity in the Conditions of a-Typical Employment - Dobrowolska, Małgorzata (European Journal of Economics and Business Studies, 2015)
Work productivity is of crucial importance to all employers regardless of what solutions they use, traditional or flexible ones. Most human resource management programs are oriented on HR tools that are favourable for employee efficiency, and hence on organizational effectiveness and productivity. When examining different psychological variables that are relevant in psychology of work and organization, popularity and productivity prove to be vital, since this variable correlates with all the remaining psychological dimensions due to continuous and intensive search for ways to improve efficiency in the work place. This article presents the results of the research carried out on n=2118 a-typical employees.
Keywords: work productivity, a-typical employment, praxeology